Adaptive Multiuser Detectors for DS-CDMA Systems - Paul Jean Etienne Jeszensky (Semina: Ciências Exatas e Tecnológicas, 2006)
This work makes a review of the main Adaptives Multi-user Detectors (MuD-Adpt) for Direct Sequence - Code Division Multiple Access (DS-CDMA) systems. The MuD-Adpt based on Minimum Mean Square Error (MMSE) and Decorrelator (MuD-Dec) are focused. Multi-user detectors show great resistance to the near-far effect and combat effectively the Multiple Access Interference (MAI). Comparative numeric results characterize the substantial performance improvement of those detectors in relation to the matched filter conventional receiver (Conv).